Falsafah Ibadat dan Hubungan Manusia - Tuhan - Idris bin Zakaria (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Not only are the religious worships obligated to every mukallaf Muslim as the sign or evidence of a faithful servant of Allah, or as the proof of Allah's existence, but these practices have their own foundation and philosophy. Both foundation and philosophy of the religious practices are intended to raise the level and status of human beings as the best creation of God compared to all other creatures. Worship needs to be practiced consistently and frequently so that it reinforces and intensifies the remembrance of God in the heart of human. The article concludes that obedient servants who always practice the religious worships will return to their original nature as pure and holy human, and will reach their position as the best creation of God.